Identification of the main fatty acids component of the cork suberine by GC/MS - Bleton, J; Mejanelle, P; Goursaud, S; Tchapla, A (ANALUSIS, 1998)
The aim of this work was to verify the presence of cork (Quercus Suber) in two samples of linoleum the beginning of the twentieth century Using GC/MS after acidic methanolysis and silylation, it was possible to identify most of the components of a modern sample of cork. The dominant is a lipid polymer: the suberin. Its monomeric composition is examined in details.
APS
Keywords: Cork; GC/MS; Quercus suber L.; suberin